Prevention and Remediation of Police Excessive Force and Similar Complaints - Russel K. Osgood (Washington University Journal of Law & Policy, 2021)
Currently, many jurisdictions do not have a basic disciplinary system in place with respect to allegations of excessive force. Even those that do have found them to be ineffective for various reasons including police mismanagement. Improving the system is complicated by the multiplicity and variability of U.S. police and sheriff departments. Osgood proposes mandating some form of a statewide or regional police force structure with better training, higher educational requirements for officer entry, less of a militarized appearance, revised review with respect to claims of excessive force, and more. Osgood describes aspects of an ideal state-wide or regional police disciplinary procedure.
Keywords: police; policing; excessive force; force; discipline; disciplinary review; police training; police education; law enforcement